2006
DOI: 10.1002/fld.1083
|View full text |Cite
|
Sign up to set email alerts
|

Solid-particle erosion in the tube end of the tube sheet of a shell-and-tube heat exchanger

Abstract: SUMMARYErosion is one of the major problems in many industrial processes, and in particular, in heat exchangers. The e ects of ow velocity and sand particle size on the rate of erosion in a typical shell-and-tube heat exchanger were investigated numerically using the Lagrangian particle-tracking method. Erosion and penetration rates were obtained for sand particles of diameters ranging from 10 to 500 m and for inlet ow velocities ranging from 0.197 to 2:95 m=s. A ow visualization experiment was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…This rise is approximately 9.5 times at volume concentration of 4%. Increasing the volume concentration from 2% to 4% resulted in a lift in total erosion to 8 times which is similar to findings by Habib, Badr, Said, Ben-Mansour, and Al-Anizi [43]. Fig.…”
Section: Initial Numerical Modelingsupporting
confidence: 91%
“…This rise is approximately 9.5 times at volume concentration of 4%. Increasing the volume concentration from 2% to 4% resulted in a lift in total erosion to 8 times which is similar to findings by Habib, Badr, Said, Ben-Mansour, and Al-Anizi [43]. Fig.…”
Section: Initial Numerical Modelingsupporting
confidence: 91%
“…This is due to the stronger recirculating flow in one half of the plenum, associating with a cross flow from one half of the plenum to the other half and a rotational flow in the inlet entrance. The particle trajectory traces captured by a high-speed digital camera (Habib et al, 2006) showed a flow pattern with one more swirl in the right half side of the tube entrance than the left half size, which well demonstrated the flow pattern simulated in this work. The simulation of gas flow in a similar heat exchanger (Bremhorst & Brennan, 2011) showed approximately symmetrical velocity and flow angle contours at tube sheet at a much higher flow rate than the present work.…”
Section: Fluid Flow and Particle Motion In The Plenumsupporting
confidence: 81%
“…It was found that high erosion only occurs at scattered small areas. The simulations of erosion in a heat exchanges with 824 tubes (Habib et al, 2005) and in a heat exchanger with 38 tubes (Habib et al, 2006) also showed a location profile of the critical erosion tubes and the serious erosion only occurred on a few tubes. Figure 7 shows that HE1 has the most serious erosion on the tube sheet, and the maximum erosion rate of HE3 is the lowest.…”
Section: Erosion Rate and Damage Locationmentioning
confidence: 88%
See 2 more Smart Citations